P-glycoprotein in sheep liver and small intestine: gene expression and transport efflux activity. - Ballent, Mariana (2013)
The role of the transporter P-glycoprotein (P-gp) in the disposition kinetics of different drugs therapeutically used in veterinary medicine has been demonstrated. Considering the anatomo-physiological features of the ruminant species, the constitutive expression of P-gp (ABCB1) along the sheep gastrointestinal tract was studied. Additionally, the effect of repeated dexamethasone (DEX) administrations on the ABCB1 gene expression in the liver and small intestine was also assessed. The ABCB1 mRNA expression was determined by real-time quantitative PCR. P-gp activity was evaluated in diffusion chambers to determine the efflux of rhodamine 123 (Rho 123) in the ileum from experimental sheep. The constitutive ABCB1 expression was 65-fold higher in the liver than in the intestine (ileum). The highest ABCB1 mRNA expression along the small intestine was observed in the ileum (between 6- and 120-fold higher). The treatment with DEX did not elicit a significant effect on the P-gp gene expression levels in any of the investigated gastrointestinal tissues. Consistently, no significant differences were observed in the intestinal secretion of Rho 123, between untreated control (Peff S-M = 3.99 × 10-6 ± 2.07 × 10-6) and DEX-treated animals (Peff S-M = 6.00 × 10-6 ± 2.5 × 10-6). The understanding of the efflux transporters expression and activity along the digestive tract may help to elucidate clinical implications emerging from drug interactions in livestock.